Representation and participation in formulating Nepal's REDD+ approach. (22nd July 2019) - Satyal, Poshendra; Corbera, Esteve; Dawson, Neil; Dhungana, Hari; Maskey, Gyanu
ABSTRACT: REDD+ is an international policy aimed at incentivizing forest conservation and management and improving forest governance. In this article, we interrogate how newly articulated REDD+ governance processes established to guide the formulation of Nepal's REDD+ approach address issues of participation for different social groups. Specifically, we analyse available forums of participation for different social groups, as well as the nature of their representation and degree of participation during the country's REDD+ preparedness phase. We find that spaces for participation and decision-making in REDD+ have been to date defined and dominated by government actors and influential civil society groups, whereas the influence of other actors, particularly marginalized groups such as Dalits and women's organizations, have remained limited. REDD+ has also resulted in a reduction of influence for some hitherto powerful actors (e.g. community forestry activists) and constrained their critical voice. These governance weaknesses related to misrepresentation and uneven power relations in Nepal cast doubt on the extent to which procedural justice has been promoted through REDD+ and imply that implementation may, as a consequence, lack the required social legitimacy and support. We discuss possible ways to address these shortcomings, such as granting greater prominence to neglected civil society forums within the REDD+ process, allowing for an increase in their influence on policy design, enhancing capacity and leadership of marginalized groups and institutionalizing participation through continued forest governance reform. Key policy insights Participation is a critical asset in public policy design. Ensuring wide and meaningful participation can enhance policy legitimacy and thus its endorsement and potential effective implementation. Fostering inclusive processes through dedicated forums such as multi-stakeholder groups can help overcome power dynamics. While REDD+ is open to participation by different actors through a variety of formal means, many countries lack a clear framework for participation in national policy processes. Nepal's experience with representation and participation of non-state actors in its REDD+ preparedness programme provides useful insights for similar social and policy contexts.